Investigation of the dynamics of COVID-19 with SEIHR nonsingular and nonlocal kernel fractional model. (2nd November 2022) - Deressa, Chernet Tuge; Duressa, Gemechis File
ABSTRACT: We considered an SEIHR mathematical model to investigate the dynamics of COVID-19. Real data of COVID-19 confirmed cases are fitted to the model. The basic reproductive number is approximated to be R 0 ≈ 2.16 . The most globally sensitive parameter of the basic reproductive number is the incubation period of coronavirus. The Atangana Baleanu fractional derivative in Caputo sense (ABC) representation of the model is formulated, and a numerical approximation developed by Toufik and Atangana is used. It is shown that decreasing the fractional-order leads to decreasing the infection of the virus in the infected compartments.